Diagnostic criteria of pediatric migraine without aura - Senbil, Nesrin; Gürer, Yahya Kemal Yavuz; Aydin, Omer Faruk; Rezaki, Bengii; Inan, Levent (The Turkish Journal of Pediatrics, 2006)
The objectives of this study were to assess the validity of the International Classification of Headache Disorders-I (ICHD-I) and the International Headache Society-Revised (IHS-R) criteria and to evaluate the other headache features that are not included in these criteria for migraine without aura in the pediatric population. One hundred and thirty-two children who referred to our clinic with the complaint of chronic or recurrent headache were evaluated. Clinical diagnosis of the pediatric neurologist was used as the gold standard in evaluating the validity of ICHD-I and IHS-R criteria and the other headache features. After eliminating patients with other migraine types, secondary headache, and missing data, 92 patients were included in the study according to their records. Sixty-one children (66.3%) were diagnosed as migraine without aura. Using the clinical diagnosis as the gold standard, the specificity of ICHD-I criteria was detected as 93.5%, while the sensitivity was detected as 36.1%. IHS-R criteria had 90.3% specificity and 78.7% sensitivity. Relief of headache with sleeping or lying down in a dark, quiet room was found to be the highest specific and sensitive factor of the other headache features not included in these criteria. IHS-R criteria were found to be more valid in the diagnosis of migraine without aura than ICHD-I criteria. IHS-R criteria are recommended both in clinical practice and in the studies requiring migraine without aura case definitions in the pediatric population.